2008
DOI: 10.1097/pas.0b013e318058a96b
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Prostate

Abstract: Pure small-cell carcinoma (SCC) of the prostate is a rare entity and one of the most aggressive malignancies of the prostate. Histologically, prostatic SCCs of the prostate are part of a spectrum of anaplastic tumours of the prostate and are similar to SCCs of the lungs. In most cases, SCC of the prostate is associated with conventional prostatic adenocarcinoma. Both components of these mixed tumours frequently share molecular alterations such as ERG gene rearrangements or AURKA and MYCN amplifications, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
130
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(142 citation statements)
references
References 68 publications
3
130
2
Order By: Relevance
“…A series 44 cases of SCC of the urinary bladder cases study also showed: TTF-1+, 11 (25%); synaptophysin+, 22 (50%) [[8]]. TTF-1 is often positive in prostate small cell carcinomas [[9],[10]]. Prostate-specific immunostains (such as PSA, p501s and PSMA) are positive in only a minority of small cell carcinoma (approximately 20–25%) [[10],[11]] AR and NKX3-1 were not expressed in the majority of small cell carcinoma, although the majority of the concurrent acinar foci were positive for these markers [[2]].…”
Section: Discussionmentioning
confidence: 99%
“…A series 44 cases of SCC of the urinary bladder cases study also showed: TTF-1+, 11 (25%); synaptophysin+, 22 (50%) [[8]]. TTF-1 is often positive in prostate small cell carcinomas [[9],[10]]. Prostate-specific immunostains (such as PSA, p501s and PSMA) are positive in only a minority of small cell carcinoma (approximately 20–25%) [[10],[11]] AR and NKX3-1 were not expressed in the majority of small cell carcinoma, although the majority of the concurrent acinar foci were positive for these markers [[2]].…”
Section: Discussionmentioning
confidence: 99%
“…Although prostatic markers such as prostatic acid phosphatase, PSA, prostate-specific membrane antigen, and prostein may be helpful in establishing the prostatic origin, the majority of prostatic SCCs are negative for these markers. 5 Prostatic SCC was initially reported to be negative for thyroid transcription factor-1, 18 nonetheless subsequent studies have found that most prostatic SCCs express TTF-1. 6 A recent study found that CD44 may be a unique feature of prostatic SCC, but a substantial number of lung SCCs are also positive for CD44.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although lung SCC is far more common than prostatic SCC, in the absence of a lung primary, the presence of SCC in a prostate specimen is most likely to be a prostatic primary. 5 The involvement of prostate by lung SCC is rare and only occurs in the setting of widespread metastases. Hence, the distinction of prostatic SCC from non-prostatic origin has limited value in the prognosis and treatment of SCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is androgen receptor (AR) negative, NE PCa is naturally androgen independent. Although the vast majority of primary human PCa are adenocarcinomas, immunohistochemical evidence of NE differentiation (NED) can be often found in human PCa, and PCa exhibiting NED is associated with poor prognosis (19, 20). Rapid autopsy of hormone-refractory metastatic PCa has shown NED in most cases (21), and patients that fail androgen deprivation therapy can develop NE cancer and adenocarcinoma with NED (22).…”
Section: Introductionmentioning
confidence: 99%